The Potential for Pocket Parks to Increase Physical Activity. Issue 3 (January 2014) - Cohen, Deborah A.; Marsh, Terry; Williamson, Stephanie; Han, Bing; Derose, Kathryn Pitkin; Golinelli, Daniella; McKenzie, Thomas L.
Purpose: To assess the use of new pocket parks in low-income neighborhoods. Design: The design of the study was a quasi-experimental post-test only comparison. Setting: Los Angeles, California, was the setting for the study. Subjects: Subjects were park users and residents living within .5 mile of three pocket parks and 15 neighborhood parks. Intervention: The creation of pocket parks. Measures: We used the System of Observing Play and Recreation in Communities (SOPARC) tool to measure park use and park-based physical activity, and then surveyed park users and residents about their park use. Analysis: We surveyed 392 and 432 household members within .5 mile of the three pocket parks before and after park construction, respectively, as well as 71 pocket park users, and compared them to 992 neighborhood park users and 342 residents living within .5 mile of other neighborhood parks. We compared pocket park use to playground area use in the larger neighborhood parks. We used descriptive statistics and generalized estimating equations for the analysis. Results: Overall, pocket park use compared favorably in promoting moderate-to-vigorous physical activity with that of existing playground space in nearby parks, and they were cost-effective at $0.73/MET hour (metabolic equivalent hour) gained. Pocket park visitors walked an average of .25 miles to get to a park. Conclusions: Pocket parks, when perceived as attractive and safe destinations, may increase physical activity by encouraging families with children to walk there. Additional strategies and programs may be needed to encourage more residents to use these parks.